2017
DOI: 10.7595/management.fon.2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

ARWU vs. Alternative ARWU Ranking: What are the Consequences for Lower Ranked Universities?

Abstract: Decision makers and government representatives use numbers in the process of policy making in various spheres of life (Porter, 1995). Higher education is just one of thoe that saw the introduction of scores into its assessment methods through university rankings (Daraio & Bonaccorsi, 2017). Since 2003 and the first global university ranking, the university rankings have proliferated. The three world-acknowledged and most often analysed rankings are the Academic Ranking of World Universities (ARWU), the Times H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Namely, the question, which arises, is whether one weighting scheme fits 50 and 500 entities? A recently conducted in-depth analysis of the ARWU and Alternative ARWU rankings which rank 500 entities (universities) showed that there are significant differences between groups of 100 universities and that the length of the ranked universities should be taken into account when creating a composite index (Maricic et al, 2017). Therefore, herein, we aim to expand the current literature on the topic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the question, which arises, is whether one weighting scheme fits 50 and 500 entities? A recently conducted in-depth analysis of the ARWU and Alternative ARWU rankings which rank 500 entities (universities) showed that there are significant differences between groups of 100 universities and that the length of the ranked universities should be taken into account when creating a composite index (Maricic et al, 2017). Therefore, herein, we aim to expand the current literature on the topic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our research hypothesis is that one weighting scheme does not fit all entities when the composite index ranks a large number of entities. The hypothesis of the research is starting to attract attention within the scientific community (Maricic et al, 2017). Our proposed approach is to firstly divide entities into groups and secondly, to rank and weight them accordingly within each group.…”
Section: Introductionmentioning
confidence: 99%
“…They explained several potential directions to approach the robustness issue, such as defining the range for the possible rank of alternatives(Beynon and Barton, 2008) or by indicating various intensity measures of the dominance relation within the method(Ahn and Park, 2008). The importance of this line of research is not solely related to MCDA methods and it can be seen as a state of the art question in academia recently (for example ARWU ranking sensitivity analysis has been of interest in a number of studies such asDobrota & Dobrota, 2016;Maricic et al, 2017;Zornic et al, 2014).…”
mentioning
confidence: 99%